Upgrading pyrolysis bio-oil through hydrodeoxygenation (HDO) using non-sulfided Fe-Co/SiO2 catalyst. (15th October 2017) - Cheng, Shouyun; Wei, Lin; Julson, James; Rabnawaz, Muhammad
Highlights: Fe-Co/SiO2 catalyst with medium acidity was more effective for bio-oil upgrading. Co-loading of Fe and Co on SiO2 support improved catalyst performance. Catalyst showing the best catalytic activity had a Fe/Co mole ratio of 1. Biofuel produced by Fe-Co(1)/SiO2 had the higher hydrocarbons content at 22.44%. The mechanism of bio-oil HDO on Fe-Co/SiO2 catalysts is proposed. Abstract: Hydrodeoxygenation (HDO) is an effective route to upgrade bio-oil to hydrocarbon bio-oil, but the development of efficient catalysts for bio-oil HDO still remains a challenge. In this study, non-sulfided Fe-Co/SiO2 catalysts were used to upgrade bio-oil using HDO. A series of Fe-Co/SiO2 catalysts with different Fe/Co mole ratios were prepared, characterized and evaluated. The Fe and/or Co loading did not change SiO2 crystalline structure. The Fe and/or Co metals increased the amount and strength of Fe-Co/SiO2 catalyst acidity. Physicochemical properties of upgraded bio-oils produced using Fe-Co/SiO2 catalysts such as water content, total acid number, viscosity and higher heating values improved in comparison to raw bio-oil. Bimetallic Fe-Co/SiO2 catalysts resulted in better HDO performance than monometallic Fe/SiO2 or Co/SiO2 catalysts. This was due to the synergistic effect of Fe and Co occurring on the SiO2 support. Fe-Co/SiO2 catalyst having medium amount of acidity was more effective for bio-oil upgrading. The highest hydrocarbons content produced using Fe-Co(1)/SiO2 catalyst was 22.44%. The mechanism of bio-oil HDO on Fe-Co/SiO2 catalysts is proposed.